PENYERANGAN RUSIA TERHADAP UKRAINA DITINJAU DARI HUKUM INTERNASIONAL - Diana Octavia Situmeang; Maria Maya Lestari; Zulfikar Jayakusuma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Sending Russian military troops into a sovereign state territory to carry out occupationsand special military operations according to international law is a form of violation of statesovereignty or what is known as an invasion. This is an act that violates international peaceand is rejected by the international community because it gives many bad influences to theinternational legal order which influence one another. Besides that, the act of attacking thesovereignty of other countries is also contrary to the theory of sovereignty to internationalcustoms.The type of research used by the author is normative legal research or what is knownas "legal research". which means that legal research is conceptualized as what is written inlaws and regulations (law in book) or law. Regarding how International Law responds to theattack carried out by Russia against Ukraine as a violation of International Law which isdetrimental to many parties, especially Ukraine.The status of the attack carried out by Russia against Ukraine according tointernational law is aggression according to what is stipulated in the UN General Resolution,because the invasion or military attack carried out by Russia against Ukraine is a form ofaggression recognized by international law. As a violation of international law in general,Russia as the aggressor must be legally responsible. The legal responsibility of the aggressoraccording to International Law is regulated as the definition of aggression was first regulatedin the UN General Resolution by giving power to the UN Security Council. Legal accountabilityto the aggressor state can also be carried out through its implementation at the ICJ(International Court of Justice) and individual accountability at the ICC (InternationalCriminal Court).